828 Non-wearing of flotation devices and swimming ability of boating immersion victims in Canada. (1st September 2016) - Barss, Peter; Olsen, Karlyn; Hamilton, Jane; Dalke, Shelley
Abstract : Background: Boating is the most frequent activity for water-related immersion deaths in Canada. Central in immersion/drowning is non-wearing of personal flotation devices (PFDs). Anecdotal observation of frequent non-wearing among victims led to quantitive assessment using negative binomial and Poisson regression models. Methods: Annual Red Cross collection of 1991–2010 Canadian coroner data was by structured questionnaire. Analysis included ten variables in the final model. Results: There were 2678 recreational and daily living boating immersion deaths during 1991–2010. Certain variables significantly increased the odds of properly wearing a PFD and others decreased them. Controlling for all other variables, victims with average swimming ability had 1.93 times the odds of wearing compared with non and weak swimmers combined (95% CI: 1.29–2.87). Strong swimmers had 1.90 times the odds of wearing compared with non/weak swimmers (95% CI: 1.06–3.40). Conclusion: It was surprising that boating victims with low swimming ability were less likely than swimmers to have worn a flotation device. It is possible, but remains to be established, that poor swimmers were less likely to have participated in a swimming course, which included the main elements of water safety for boating and other activities.